Growth of InN Nanowires with Uniform Diameter on Si(111) Substrates: Competition Between Migration and Desorption of In Atoms. Issue 21 (6th April 2017) - Gao, Fangliang; Wen, Lei; Xu, Zhenzhu; Han, Jinglei; Yu, Yuefeng; Zhang, Shuguang; Li, Guoqiang
Abstract : The effects of the growth parameters on the uniformity and the aspect ratio of InN nanowires grown on Si(111) substrates have been studied systematically, and a modified quasi‐equilibrium model is proposed. The growth temperature is of great importance for both the nucleation of the nanowires and the migration of In and N atoms, thus affecting the uniformity of the InN nanowires. In order to improve the uniformity of the InN nanowires, both traditional substrate nitridation and pre‐In‐droplet deposition have been implemented. It is found that the substrate nitridation is favorable for the nucleation of InN nanowires. However, the initial In atoms adhered to the substrate are insufficient to sustain the uniform growth of the InN nanowires. We have found that the initial In droplet on the substrate is not only advantageous for the nucleation of the InN nanowire, but also favorable for the In atom equilibrium between the initial In droplets and the direct In flux. Therefore, InN nanowires with a uniform aspect ratio and optimal diameter can be achieved. The results reported herein provide meaningful insights to understanding the growth kinetics during the InN nanowires growth, and open up great possibilities of developing high‐performance group III‐nitride‐based devices. Abstract : InN nanowires with a uniform aspect ratio and optimal diameter have been grown by molecular beam epitaxy. By carefully controlling the In atom equilibrium between the initial In droplets and the direct In flux results in straight nanowires without any tapering. A revised quasi‐equilibrium model is also proposed to better understand the growth kinetics during InN nanowires growth.